The Use of Digital Learning Platform as Communication Media for Generation Z at PB. Soedirman Islamic High School, Jakarta - Iswadi, Iswadi; Iriansyah, Herinto Sidik; Erman Anom, Erman Anom (Didaktika Religia, 2024)
The objective of this study is to assess the efficacy of utilising digital learning platforms as a medium for communication in Islamic education, with a particular emphasis on Generation Z teachers at PB. Soedirman Islamic High School, Jakarta. This generation is known as digital natives, who are highly adept at navigating information technology. The research method employed is a case study with a qualitative approach, comprising interviews, participatory observation, and surveys. The findings indicate that Generation Z teachers at PB. The respondents at Soedirman Islamic High School, Jakarta, indicated that they felt at ease and benefited from the utilisation of digital learning platforms for communication and learning purposes. The aforementioned platforms facilitate more expedient and effective communication. Nevertheless, certain challenges were also identified, including the potential for unclear communication and the risk of information overload. The factors affecting the effectiveness of communication through digital platforms were identified, including the teachers’ technological competence, the design of the digital platforms, the organisational culture, and the provision of adequate training and support. This research is consistent with the Technology Acceptance Model, which posits that perceived ease of use and usefulness have a significant effect on technology acceptance. The results of this study provide practical implications for optimising the use of digital learning platforms through continuous training, intuitive platform design, and digital culture support within the organisation. Consequently, digital platforms can enhance the performance and job satisfaction of Generation Z teachers.